Relativistic Wave Propagation in Anisotropic Two-Component Magnetohydrodynamics Plasmas - Temesgen Kassaw; Gebretsadkan Woldemhret (Advances in Mathematical Physics)
This paper investigates the instabilities and characteristics of relativistic linear waves of two-component plasma by assuming the plasma to be in-viscid, homogeneous, collision-less, and magnetized. To do this, by taking moments of the relativistic Vlasov equation, the basic equations of the two-component relativistic an-isotropic plasma are derived. The linearized equations are analyzed for small perturbation under the assumption of the plasma which is initially at rest. After we derived the dispersion relations, different wave modes and instabilities are discussed analytically and numerically presented as well.